Composite fault diagnosis method for rolling bearing - ZHANG LIBIN; CHAI HAOQI; MA ZEPENG; FU LEI; ZHANG PENGSHUAI (2023)
The invention discloses a compound fault diagnosis method for a rolling bearing, and the method comprises the steps: carrying out the noise reduction of an original vibration signal through employing a singular value decomposition method, and carrying out the optimization of related parameters in the maximum correlation kurtosis deconvolution through employing a fish swarm optimization algorithm; and separating a single fault signal from a composite fault signal by using optimized maximum correlation kurtosis deconvolution, performing envelope analysis on all separated single fault components to identify a corresponding fault type, and integrating results, thereby realizing composite fault diagnosis of the rolling bearing. 本发明公开了一种滚动轴承的复合故障诊断方法，该方法使用奇异值分解方法对原始振动信号进行降噪处理，使用鱼群优化算法对最大相关峰度反卷积中的相关参数进行优化，使用优化后的最大相关峰度反卷积将单一故障信号从复合故障信号中分离，对分离出的所有单一故障分量进行包络分析识别对应故障类型并将结果综合起来，从而实现滚动轴承的复合故障诊断。